2021
DOI: 10.3390/ma14061533
|View full text |Cite
|
Sign up to set email alerts
|

Durability of Epoxy Adhesives and Carbon Fibre Reinforced Polymer Laminates Used in Strengthening Systems: Accelerated Ageing versus Natural Ageing

Abstract: This work addresses the durability of structural epoxy adhesives and carbon fibre reinforced polymer (CFRP) laminates typically used in strengthening of existing reinforced concrete structures exposed to natural ageing. The experimental program included four natural (real) outdoor environments inducing ageing mainly caused by carbonation, freeze-thaw attack, elevated temperatures, and airborne chlorides from seawater. Moreover, a control (reference) environment (20 °C of temperature and 55% of relative humidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 55 publications
0
11
1
Order By: Relevance
“…Some authors have reported flexural strengths of 0.5 to 0.6 GPa, 29 and the values of the present study are nearly twice the values reported by the authors. However, the flexural modulus ranges between 30 and 35 GPa, 29,30 and the values of the present work are relatively lower. The use of graphene oxide (GO) and twill carbon fiber accounts for the differences in the values of the flexural properties.…”
Section: Flexural Properties Of Compositescontrasting
confidence: 59%
“…Some authors have reported flexural strengths of 0.5 to 0.6 GPa, 29 and the values of the present study are nearly twice the values reported by the authors. However, the flexural modulus ranges between 30 and 35 GPa, 29,30 and the values of the present work are relatively lower. The use of graphene oxide (GO) and twill carbon fiber accounts for the differences in the values of the flexural properties.…”
Section: Flexural Properties Of Compositescontrasting
confidence: 59%
“…Fiber reinforced composite elements, intended as reinforcements for civil engineering infrastructures, based on unidirectional carbon fibers and a vinyl-ester matrix, were subjected to different outdoor exposure (four locations in Portugal, characterized by diverse environmental and pollution conditions, employing a two years exposure time) and accelerated aging procedures (i.e., immersed in water at 20 °C or collecting data from previous studies reported in literature), comparing the effects of the different weathering regimes [ 50 ]. The Authors of the study reported that the accelerated aging protocols generally caused a greater degradation in mechanical (measured in tensile mode) properties, especially the tensile strength, with respect to the exposure to natural aging, irrespective to the exposure site.…”
Section: Comparison Between On Field Durability Tests With Accelerated Proceduresmentioning
confidence: 99%
“…Cold-cured structural epoxy resins are, in fact, the adhesives typically employed in civil engineering applications to apply a FRP element on the surface to strengthen or as matrices for in-situ formed FRPs; they display peculiar characteristics, such as very long curing times to achieve a not complete conversion degree of epoxy groups and a glass transition temperature never exceeding 65–70 °C [ 51 ]. Even for this class of polymeric materials, the mechanical data collected after natural or artificial aging regimes were found to be not comparable, the accelerated ageing tests leading to greater reductions in mechanical properties if compared to the effects due to natural exposure [ 50 ]. Similar results have been previously reported by [ 52 ] that tried to correlate the effects of natural exposure (carried out in two different locations in South Italy) and artificial aging on thermal (i.e., Tg) and mechanical (in flexural mode) characteristics of cold-cured epoxy adhesives.…”
Section: Comparison Between On Field Durability Tests With Accelerated Proceduresmentioning
confidence: 99%
“…One of the other lines of work in this field is analyzing, under different orientations, the behavior of the adhesive joints in composite materials subjected to different degradation processes, such as humidity and its effects in the process of delamination under pure fracture modes [ 28 ], exposure to a saline environment [ 29 ], the absorption of water in joints with hybrid composite materials [ 30 , 31 ], the effect of temperature [ 32 , 33 ] and the combination of the effects of humidity and temperature [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%